Synthesis and Characterization of The MCM-48 and Modified NH2 - Sari, Andi Y.P.; Taba, Paulina; Budi, Prastawa (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2015)
This research aims to synthesize and characterize MCM-48 modified with the group-NH2. Synthesis of MCM-48 and its modification by NH2 conducted by Ryoo methods where is the salt of Ludox HS40 solution mixed with NaOH solution then heated, followed by making mixture of CTAB and Triton X-100. The resulting gel mixture is heated at temperature of 100 °C for 24 hours. The reaction mixture added 30% acetic acid until pH 10. Then the mixture was heated at 100 °C for 24 hours then cooled at room temperature. MCM-48 mesoporous silica that has formed was filtered, washed with distilled water and dried at 120 °C. MCM-48 mesoporous silica characterized using XRD and FTIR. Modification of MCM-48-NH2 was done by adding 3-APTES into mesoporous silica. XRD analysis results showed that the characteristic peaks at 2 theta 2.4o have Miller indices 211and several peaks with low intensity. These peaks are typical peak for MCM-48. By FTIR showed the specific areas observed for organic molecules (surfactant) in MCM-48 synthesized; CH span (2800-3100 cm-1) and CH bending (1400 to 1500 cm-1). C-H bending vibration was observed in 1645; 1512 and 1481 cm-1. The success of modified MCM-48-NH2 was shown by the appearance of two absorption bands at wave numbers 3368 and 3424 cm-1 which indicate the presence of a primary amine or an amino group (-NH2) in the mesoporous channel